ANALISIS DEDIKASI POLA ASUH ORANG TUA TERHADAP KESEHATAN MENTAL ANAK DISABILITAS DI BANGKALAN - Nadya Wulandari (Journal of Student Research, 2024)
. Parents are the main and first educators of their children, because it is from them that the child first receives education. The role of parents as the main and first educators for children is also because heredity they are destined to be parents who give birth. So by nature, inevitably parents who are the main and first responsible for children can receive education. The dedication of parents in caring for children with special needs has a very impact on the survival of children with special needs in the future, the child's growth and development process will be affected if parents cannot determine the right caregiver style. Children who have unique needs need additional care from classmates, parents, teachers, and other family members. In order for children with special needs to reach their full potential, it is important that they should be given support rather than ignored or ostracized. Children suffering from physical or mental health problems should receive different care than other children. Similarly, to improve learning achievement and, in particular, to give priority to the improvement of physical and mental growth they must be equipped with the necessary means and facilities for their activities.